Civic participation and apathy in South African Local Government : a case of Mankweng Township in Polokwane Local Municipality - Sekatle, Kananelo (My University, 2022)
The purpose of local government is to promote the realisation of human rights, socio-economic development, and cultural, civil, and political rights to improve communities (Ojochenemi, 2016). Residents are known to be dissatisfied with the poor quality services provided by the local government, which has resulted in unending protests and apathetic citizens. The research focused on the nature of civic participation and the causes of civic apathy in Mankweng Township, as well as the mechanisms that can be implemented to increase civic participation in Mankweng Township and how citizens‟ awareness can be raised. The study discovered that there is high levels of civic apathy in Mankweng Township, which hinders the operation of the municipality, whether it is the service delivery process or the municipality's responsiveness to the citizen's needs, based on the literature, distributed questionnaires, and conducted interviews. Civic apathy also leads to poor governance, which leads to distrust between the government and the citizens. Recommendations were made to help Mankweng Township overcome the challenges of civic apathy; one of these recommendations included encouraging township participation.
Thesis (MPA.) -- University of Limpopo, 2022
Keywords: Civic participation; Apathy; South African Local Government; Political rights; Poor service delivery; Armed forces -- Civic action; Apathy; City planning; Local government -- South Africa -- Limpopo; Political rights -- South Africa -- Limpopo